2012
DOI: 10.1111/j.1537-2995.2012.03840.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serologic markers for hepatitis B and C viruses in Brazilian blood donors and incidence and residual risk of transfusion transmission of hepatitis C virus

Abstract: Background We evaluate the current prevalence of serological markers for HBV and HCV in blood donors and estimated HCV incidence and residual transfusion-transmitted risk at three large Brazilian blood centers. Material and Methods Data on whole blood and platelet donations were collected from January through December 2007 and analyzed by center, donor type (replacement vs. community), age, sex, donation status (first-time vs. repeat), and serological results for HBsAg, anti-HBc and anti-HCV. HBV (HBsAg+/ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 31 publications
10
39
1
Order By: Relevance
“…These discrepancies are probably due to an overestimation of rates in past studies based only upon screening results or to differences in donor selection strategies. The age association with prevalence of HCV markers is in accordance with recent findings in Brazil (de Almeida-Neto et al, 2013) and may be explained by higher HCV transmission and prevalence in the past compared to the present. This hypothesis of lower current incidence is supported by the low proportion (only 50%) of viremic donors observed among confirmed positive subjects in this study.…”
Section: Discussionsupporting
confidence: 90%
“…These discrepancies are probably due to an overestimation of rates in past studies based only upon screening results or to differences in donor selection strategies. The age association with prevalence of HCV markers is in accordance with recent findings in Brazil (de Almeida-Neto et al, 2013) and may be explained by higher HCV transmission and prevalence in the past compared to the present. This hypothesis of lower current incidence is supported by the low proportion (only 50%) of viremic donors observed among confirmed positive subjects in this study.…”
Section: Discussionsupporting
confidence: 90%
“…The present study showed that the City of Criciúma had the highest HIV and HCV risk among blood donors. An HCV incidence of 3.11 per 100,000 donor-years and an HCV residual risk of 0.5 per 100,000 were reported for the capitals of the federal States of São Paulo, Rio de Janeiro and Minas Gerais in 2007, along with a downward trend over time 17 . This fi nding is in line with similar trends among HEMOSC blood donors.…”
Section: Discussionmentioning
confidence: 99%
“…Research on blood donors has shown a predominance of male donors, with a prevalence of 63.9-71.3% [32][33][34][35] . With respect to ethnicity, 96.2% of blood donors in the present study were Caucasian, which is consistent with the 2010 census in which 83.9% of the population of the State of Santa Catarina declared themselves as Caucasian 36 .…”
Section: Discussionmentioning
confidence: 99%